If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -1) + (2x + 1) = 8x + -4 Reorder the terms: (-1 + 4x) + (2x + 1) = 8x + -4 Remove parenthesis around (-1 + 4x) -1 + 4x + (2x + 1) = 8x + -4 Reorder the terms: -1 + 4x + (1 + 2x) = 8x + -4 Remove parenthesis around (1 + 2x) -1 + 4x + 1 + 2x = 8x + -4 Reorder the terms: -1 + 1 + 4x + 2x = 8x + -4 Combine like terms: -1 + 1 = 0 0 + 4x + 2x = 8x + -4 4x + 2x = 8x + -4 Combine like terms: 4x + 2x = 6x 6x = 8x + -4 Reorder the terms: 6x = -4 + 8x Solving 6x = -4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 6x + -8x = -4 + 8x + -8x Combine like terms: 6x + -8x = -2x -2x = -4 + 8x + -8x Combine like terms: 8x + -8x = 0 -2x = -4 + 0 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| 3i^2+15/6-3i | | 7(x-1)=6x | | x^2+15/6-x | | 3z+3-z=10+z-5 | | 36=2(3.14)r | | 3x-13=2x | | 7g+1-5g=-8 | | -X^2-12X-20=0 | | 73.14/23 | | x/3+12/1=-x/3 | | -[5z-(15z+6)]=6+(9z+0) | | (-11-16)+5= | | 5x/7+12/7=-13/7 | | -4(y+2)=-3y-1 | | 1-6x-13= | | -4(x-6)=-4x+24 | | ln(3x+6)=3 | | 41.5/5 | | 5x+2=8x-4x | | 3y+7x=13 | | 5x+4+4x=31 | | 10.98/3.4 | | x+x+1=x+2+24 | | y=x^2+8x-11 | | 35/8x12/15 | | -1.2r=6.0 | | x^2+8x-11=y | | 4=2y+105 | | 4=2y+70 | | -12r=6.0 | | 4=2y+35 | | 0=81+9y-7x |